Numerical Modeling of Wave Reflection from Sloped Impermeable Seawalls Using the SPH Method: Case Study of Chabahar Port - Behrouz Aghaei; Afshin Mohseni Arasteh; Kamran Lari; Masoud Torabi Azad (Advances in Civil Engineering)
In this research, a comprehensive study is performed to investigate the interaction of regular waves with the impermeable seawall of the Chabahar port. First, a MIKE 21 SW model is used to transform the deep-water wave data to the nearshore zone. Then, the interaction of waves with the seawall is simulated using a well-known numerical smoothed particle hydrodynamics model named DualSPHysics. After validating the numerical results with the experimental data, a parametric study is performed to evaluate the effects of the wave height, wave period, and the slope of the seawall on the water level fluctuations and the wave reflection coefficient. The results showed that increasing the wave height slightly decreases the reflection coefficient. Meanwhile, a direct relationship was found between the wave height and the water level fluctuations near the wall. Generally, increasing the wave period resulted in higher reflection coefficients and water level fluctuations. Both the reflection coefficient and the water level fluctuations are greatly dependent on the slope of the seawall. Steeper slopes resulted in higher reflection coefficients and lower water level fluctuations near the seawall.